An eco-friendly process for zerovalent bismuth nanoparticles synthesis. (10th October 2018) - Reverberi, Andrea Pietro; Varbanov, Petar Sabev; Lauciello, Simone; Salerno, Marco; Fabiano, Bruno
Abstract: A two-pot bismuth nanoparticle synthesis based on a combination of a bottom-up method and a disaggregation technique is proposed. These steps are sequential in time and are operated in an aqueous and organic solvent, respectively. In the first phase, a cementation process with aluminium and zinc as sacrificial metals in compact form is carried out using mannitol, saponin and maltodextrin as eco-friendly capping agents for bismuth nanoparticles. In the second phase, a wet ball-stirring process allows obtaining a primary particles release in propylene glycol with a satisfactory stability. The products are characterized by dynamic light scattering and transmission electron microscopy for the size and by X-ray diffraction for both size and chemical composition. The diameters of bismuth nanoparticles obtained using both zinc and aluminium as reductants lie in the range of 10–120 nm independently of the capping agents. With respect to conventional one-pot processes using sacrificial metals in powder, this technique allows obtaining a high purity metallic bismuth at the end of the cementation step without requiring further purification treatments, thus avoiding a waste of chemical reagents in view of a cleaner production and sustainability. All stages of preparation are carried out at room temperature for a better energy saving and safety management. This process may represent a valid alternative to standard techniques based on noxious reductants or high temperature synthesis, thus promoting a shift towards a green nanoparticle synthesis.